Carbon Border Adjustment Mechanism (CBAM) and Its Implications for Developing Economies: A Systematic Literature Review - Danial Muhammad Wirdyansyah (Indonesian Journal of Energy, 2025)
Despite growing interest in the European Union’s Carbon Border Adjustment Mechanism (CBAM), there remains a significant research gap in reviewing its nuanced impacts on the least developed economies—particularly in terms of sectoral vulnerabilities, institutional constraints, and the absence of empirical evidence from real-world implementation. Thus, we systematically investigate the CBAM implications for developing countries through a structured literature review. We offer a novel contribution by examining CBAM’s overlooked impacts on the smallest and least developed economies, highlighting distributional effects on labor-intensive sectors and small exporters. Starting with an initial pool of 1,197 articles sourced via Publish or Perish, we apply the PRISMA and PICO frameworks to screen and refine the selection, ultimately analyzing 37 peer-reviewed articles published between 2015 and 2024 in Q1–Q3 Scopus-indexed journals. Our review identifies five major thematic concerns: trade competitiveness, industrial vulnerability, green technology access, climate justice, and policy responses. It finds that CBAM poses significant economic risks for carbon-intensive exports from the Global South, particularly in sectors such as iron, fertilizer, cement, and aluminum. Countries like Indonesia, India, China, and Vietnam face varying degrees of exposure depending on emission intensity and trade composition. We highlight the absence of embedded climate justice mechanisms and structural barriers to green technology access, which may hinder just net-zero transitions. In response, scholars recommend policy mechanisms such as revenue redistribution, differentiated carbon accounting, and international capacity-building. We conclude by contrasting CBAM with protectionist measures such as those enacted during the Trump administration, emphasizing CBAM’s environmental rationale while calling for adaptive, equitable strategies that align global climate goals with sustainable development in vulnerable economies. Our study advances academic discourse by elucidating the varied ways in which CBAM is conceptualized and debated across different scholarly perspectives. It also offers practical recommendations for policymakers—including financial assistance, technology transfer, and institutional capacity building—to better align climate ambition with the principles of development equity.